Plasmonic photoreactors-coated plastic tubing as combined-active-and-passive antimicrobial flow sterilizer. Issue 12 (2nd March 2022) - An, Xingda; Cheng, Ronghai; Liu, Pinghua; Reinhard, Björn M.
Abstract : Plasmonic photoreactor nanocomposite coating provides both active and passive antibacterial properties to plastic surfaces. Abstract : Plastic materials are ubiquitous in medical devices and consumer goods. As bacterial contamination of plastic surfaces can pose significant health risks, there is a need for effective approaches both to inactivate bacteria on plastic surfaces and to prevent colonization of plastic surfaces. In this study, we evaluate a plasmonic photoreactor coating for plastic surfaces that provides both active and passive antimicrobial effects and implement a visible light-driven antibacterial flow sterilizer. We demonstrate that this approach inactivates bacteria in an aqueous suspension passed through a photoreactor-coated polyethylene tubing, achieving log reduction values (LRVs) > 5 for both Gram-positive and -negative bacteria under resonant LED illumination. Importantly, the antimicrobial flow sterilizers do not cause a detectable loss of functionality for monoclonal antibodies that were included in this work as an example of high-value biologics that require sterilization. Under ambient light illumination, the plasmonic photoreactor coating exhibits a significant inhibitory effect on bacterial colonization and biofilm formation. The inhibitory effect was substantially weaker for mammalian cells, indicating some selectivity in the protection provided by the coating.